Characteristics of Epoxy Resin Polymer Mortar with Different Filler Materials - M, Surendar; Karthika V, Saravana; Kumar D, Naresh (International Journal of Engineering and Technology, 2018)
A binding material forms the core of any construction material as it physically, chemically and mechanically holds the mix together. From lime to cement, the binding materials used conventionally has changed and evolved. Cement is a mineral binding material which reacts with water and has to be cured over a 28-day period to attain its characteristic strength in addition to holding the mix together as a homogenous substance. An organic binding material is one in which an organic substance like resins, bitumen, etc., make a transition from a plastic state to hardened state by a physical or chemical process. In this investigation, cement is completely replaced by epoxy resin as an organic binder and specimen were cast with combinations of epoxy and different filler materials. The filler materials used are Fly Ash, Fumed Silica, GGBS, Quartz, Copper Slag and Silica Fume. The specimen were tested for compressive strength, tensile strength, Flexural Strength and Chemical Resistance. The flexural test was conducted on prisms with and without fibre subjected to three-point and four-point cyclic loading. Compressive Strength was done on cubes 40X40X40 mm on 1,3,5 and 7th days of casting. Dog-bone shaped specimens were subjected to tensile stress by a specially prepared tensile setup. The chemical resistance of the specimen was also tested by immersing it in 5% diluted solutions of Sulphuric acid, Nitric Acid and Hydrochloric acid. The main objective of this project is to analyse each mix design and deduce its suitable field of application based on its various characteristics exhibited by each mix combination.